Investigation of the boosted persulfate activation in the degradation of bisphenol A over MOF-derived cerium-doped Fe3O4 clusters with different shapes: the role of coordinatively unsaturated metal sites. (17th May 2022) - Ding, Jie; Zhu, Ying-Bo; Wang, Lei; Li, Yuan-Yuan; Ji, Wen-Xin; Yu, Zhi-Jun; Ma, Yu-Long; Sun, Yong-Gang
Abstract : A great challenge for the application of metal–organic frameworks (MOFs) as peroxymonosulfate (PMS) activators for environmental applications in pollutant removal is their stability and activity. Abstract : A great challenge for the application of metal–organic frameworks (MOFs) as peroxymonosulfate (PMS) activators for environmental applications in pollutant removal is their stability and activity. Pyrolysis of the MOF organic linkers under an inert gas atmosphere can maintain or improve the coordinatively unsaturated metal site (CUMS) activation ability of the MOFs and at the same time solve the problem of the collapsible and unstable MOF structure. Herein, we report a series of novel coordinatively unsaturated cerium-doped MIL-101(Fe(iii )) compounds (denoted as Ce-MIL-101) with different shapes, containing mixed-valence Fe(ii )/Fe(iii ) and Ce(iii )/Ce(iv ) sites, as new PMS activators, through the total release of solvent molecules under a controlled thermolysis reduction process at 500 °C under N2 to increase the number of CUMSs. The resulting rod-like cerium-doped Fe3 O4 materials exhibited superior stability and a higher number of active sites compared to octahedral cerium-doped Fe3 O4 . The XPS results reveal a growth of the oxygen vacancies (77.8%) and a large number of electron-deficient metal sites. Following the great improvement of the number of CUMSs, the performance (apparent rate constant) of CUMSs/MIL-101(Fe, Ce) in the activation of PMS for the degradation of bisphenol A (BPA) increased by a factor of up to 2.5 relative to that of pristine MIL-101(Fe). Density functional theory (DFT) calculations further clarified the nature of the PMS active sites at the atomic level. These new insights confirm a novel strategy for the synthesis of a highly active catalyst with different shapes for environmental remediation by controlling the CUMSs.